2021
DOI: 10.1182/blood-2021-146515
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection of HSCT Recipients Is Associated with High Mortality but No Detectable Cytokine Storm at Presentation

Abstract: Introduction The clinical manifestations of COVID-19 infection in recipients of allogeneic hematopoietic stem cell transplantation (HSCT) have been reported in multiple retrospective cohorts of patients, but there have been no prospective studies to date. Previous studies report that HSCT recipients are at higher risk, with cumulative incidence of death between 17-35%. Although an excessive pro-inflammatory viral response has been documented in the general population, its role in the immune inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Selected studies reported retrospective observational data from single‐centre experiences [4– 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], multicentre experiences [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] or registry data [ 7 , 8 , 42 , 43 , 44 , 45 ]. Seventeen studies [ 8 , 15 , 18 , 19 , 23 , 24 , 29 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 41 , 44 , 45 ] were from Europe (1153 patients), seven studies [ 4 , 6 , 17 , 20 , 22 ,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Selected studies reported retrospective observational data from single‐centre experiences [4– 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], multicentre experiences [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] or registry data [ 7 , 8 , 42 , 43 , 44 , 45 ]. Seventeen studies [ 8 , 15 , 18 , 19 , 23 , 24 , 29 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 41 , 44 , 45 ] were from Europe (1153 patients), seven studies [ 4 , 6 , 17 , 20 , 22 ,…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies [ 8 , 15 , 18 , 19 , 23 , 24 , 29 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 41 , 44 , 45 ] were from Europe (1153 patients), seven studies [ 4 , 6 , 17 , 20 , 22 , 25 , 36 ] were from North America (238 patients), seven studies [ 5 , 16 , 21 , 26 , 30 , 32 , 42 ] were from the Middle East (185 patients), two studies [ 28 , 40 ] were from South America (41 patients), one study [ 27 ] was from Asia (28 patients) and two studies [ 7 , 43 ] included patients from multiple regions (496 patients). Seventeen studies [ 7 , 8 , 16 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 35 , 38 , 39 , 40 , 41 , 45 ] included both adult and paediatric transplant recipients, 13 studies […”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations